Spatial Analysis of Public Libraries in Rasht City - Mahmoud Davoudi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی)
Purpose: The aim of this research was to analyze the spatial distribution of current libraries and the optimal distribution of libraries in the future in Rasht city. Methodology: In this research, the data of Rasht's existing libraries, statistical blocks of the 2015 census of the Rasht, and Rasht's spatial data were used in shape file format. This research was conducted based on the instructions of the Iran Public Libraries Foundation, 2017. Spatial statistics analysis has been used to investigate the spatial distribution of existing libraries and network analysis has also been used to determine the service range of libraries. Finally, VIKOR decision-making model was used to prioritize future service areas. Findings: The values ​​of the tests show the significance of cluster distribution of libraries in Rasht city, which indicates heterogeneous distribution based on population or distance from population centers. In fact, the distribution of libraries in Rasht is not suitable and they are mostly concentrated in the city center. There are few libraries in the south, west and north of Rasht city. Based on the criteria of distance and population for existing libraries, 4 service areas were determined (due to the proximity of some libraries to each other, their service areas were merged with each other). Considering the population of Rasht city, there is 14,991 square meters lack of library infrastructure to reach the access standard in this city. The existing libraries cover only 163,633 people (equivalent to 24.2%) of Rasht’s population, and with the development of about 3500 square meters of library space at the available libraries, 32.4% of Rasht's population will be covered by library services. By conducting network analysis and applying distance and population filters, twenty future service areas in Rasht city were proposed to cover the population of Rasht city in the most equitable way. These twenty areas will cover 442,575 people of the population of Rasht city, which includes 65.3% of the population of Rasht, and if they are realized and the infrastructure level of the current libraries is increased, a total of 661,943 people (97.7%) of the population of Rasht city will be covered by public libraries services. In determining the priority of the future service areas, the population is more important than the distance, and respectively, the areas with the largest population in the south, west, north and northeast of Rasht city are in the first six priorities for the construction of new libraries, and marginal areas in the north of Rasht is the last priority due to its lower population and proximity to existing libraries. 2.3% of the population of Rasht, including 15,322 people do not have the necessary population and distance criteria, and currently it is not possible to propose the establishment of a new library for them, who are mainly located in the south of Rasht city. Originality/value: Conducting land use planning researches is the basis of future planning. Lack of this type of studies and lack of foresight will lead to waste of resources and duplication in different projects. According to the basic criteria, this research has determined the amount of library infrastructure based on the population, the amount needed to increase the infrastructure of existing libraries and also the number and area of ​​new libraries in order to cover the needs of the population of Rasht city. By doing it, libraries can be expanded in principle in Rasht and new libraries can be established at the right areas of the city.